The Xenophobic Attacks on African Immigrants - Emmanuel Michael Massay; Novri Susan (Advanced Studies on Socio-Economy Development, 2023)
Since the country's xenophobic violence in 2008, the 2019 xenophobic assaults are a new reminder of South Africa's anti-immigrant prejudice. Xenophobia threatens refugees, asylum seekers, economic migrants, and other designated geographical